Design of Website-Based Queue Retrieval Application on Andi Motor using Codeigniter Framework - Andreas Gunaryo; Yusuf Kurnia (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
Conventional queues have become a common polemic in society. The duration of the process and waiting time for the queue greatly disrupts daily activities. Queuing is not fun for many people, especially if the queue is long and irregular. To deal with irregular queues, an application is needed that helps to queue more fun and has certainty of time. In the workshop, the queue retrieval system and waiting for the queue are usually done on the spot, this will not be a problem if the queue is not long, but if the queue is too long it will cause various problems. This journal discusses the design of website-based queuing applications using framework codeIgniter, where features are made based on the wishes of customers, so that this application has the purpose of facilitating customers in queuing wherever and whenever and customers will have certainty of time to queue. The design of this application uses the MVC method contained in the codeigniter framework to separate data and display and how to process it.